Optical constants of surface layer on gadolinium gallium garnet: ellipsometric study - Belyaeva, A.I.; Galuza, A.A.; Grebennik, T.G.; Yuriyev, V.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
A multiple angle ellipsometric method is used for measurements of thin film layers on substrates. The method evaluates fundamental optical constants and thicknesses of the film layers. Dielectric functions of the surface layers on the gadolinium gallium garnet (GdGaG) substrate – commonly used substrate material for rare-earth ferrogarnets (ReFeG) films, have been determined. The thickness and origin of the surface layer on the GdGaG substrate was found out. It is shown that the dielectric properties of microscopically rough layers with thicknesses ~ of 20 to 35 nm can be accurately modeled in the homogeneous thin layer approximation, but not in the effective-medium one. The precision of data was confirmed by comparing different simulations. Agreement to the third decimal point for refraction index was shown. Errors for thicknesses were not more than 3%.